2005
DOI: 10.1021/jf047938m
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution, Elimination, and Metabolism of Dietary Sodium [36Cl]Chlorate in Beef Cattle

Abstract: Two steers (approximately 195 kg) were each dosed with 62.5 or 130.6 mg/kg body weight sodium [36Cl]chlorate for three consecutive days. All excreta were collected during the dosing and 8 h withdrawal periods. The apparent radiochlorine absorption was 62-68% of the total dose with the major excretory route being urine. Parent chlorate was 65-100% of the urinary radiochlorine; chloride was the only other radiochlorine species present. Similarly, residues in edible tissues were composed of chloride and chlorate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 17 publications
4
49
0
Order By: Relevance
“…It has been assumed that chlorate salts interact directly with microbes within the gastrointestinal (GI) lumen to reduce bacterial numbers, presumably because several studies have demonstrated that chlorate is effective in both pure and mixed culture. However, multiple studies have documented the rapid and extensive removal of chlorate from the GI contents of several species through absorption (Smith et al, 2005(Smith et al, , 2006. As chlorate levels in GI tracts decrease, there is concomitant and rapid increase of chlorate in serum (Oliver et al, 2007; of orally dosed animals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been assumed that chlorate salts interact directly with microbes within the gastrointestinal (GI) lumen to reduce bacterial numbers, presumably because several studies have demonstrated that chlorate is effective in both pure and mixed culture. However, multiple studies have documented the rapid and extensive removal of chlorate from the GI contents of several species through absorption (Smith et al, 2005(Smith et al, , 2006. As chlorate levels in GI tracts decrease, there is concomitant and rapid increase of chlorate in serum (Oliver et al, 2007; of orally dosed animals.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorite was absent from tissues of cattle administered sodium [ 36 Cl]chlorate, while chlorate and chloride were the only radioactive chlo- rine species present in the urine, and chloride was the major radioactive residue in edible tissues. [27,28] Thus, chlorite is very unstable in ruminal fluid and can not be accurately determined in bovine ruminal fluid. Furthermore, observed values for all four ions at low concentrations in ruminal fluid tended to be higher than the theoretically predicted values (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorate had been determined in well water by a colorimetric method, [29] in plasma and urine by a chlorate reductive method, [30] in produce rinse water [31] and drinking water [32] by liquid chromatography, and residue studies were completed in beef cattle and swine tissues by quantifying dosed radioactive sodium [ 36 Cl]chlorate. [27,28,33] A method for quantifying chlorate and the other ions in a complex milieu such as bovine ruminal fluid is needed. The objective of this study was to develop a rapid, quantitative method for the analysis of chlorate, chlorite, nitrate and nitrite in ruminal fluid; to evaluate the loss of chlorate ion during aerobic and anaerobic incubation of chlorate-fortified ruminal fluid supplemented with added reductants that may affect the formation of chlorite and the killing of E. coli; and to determine the effect of chlorate on wildtype E. coli in ruminal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous evidence suggest chlorate resistance does not likely develop in mixed populations of gut bacteria and that even when resistant cultures generated in pure culture were added to a mixed population derived from the gastrointestinal tract, the chlorate-resistant bacteria could not compete within the highly competitive environment . Recent research examining pharmacokinetic aspects of chlorate metabolism in the mammals and aves indicate that residual chlorate in edible tissue is within established provisional safety limits (Smith et al, 2005a(Smith et al, ,b, 2006.…”
Section: Discussionmentioning
confidence: 99%